Dampak Buku Mewarnai Berbasis Pembelajaran Berdiferensiasi Terhadap Kemampuan Calistung Siswa Kelas 2 SDN 1 Kalijaga Selatan - Ochsania, Bina; Mukti, Husnul; Ramdan, Ahmad Yasar; Yazid, Muhammad (Program Studi Pendidikan Masyarakat, 2026)
Abstract: The purpose of this research is to produce a product in the form of a coloring book based on differentiated learning and to see the impact of the book on students’ abilities in learning to read, write, and count (calistung) based on the diversity of learning styles of students in grade 2 of elementary school, by using Civics learning materials as the material used in the coloring book. The research method used in this research is Reseach and Development (R&D), with the ADDIE model. The final result of this research is a coloring book based on differentiated learning on the reading, writing, and arithmetic abilities of the 2nd grade students of SDN 1 Kalijaga Selatan. Based on the analysis of the results of the material experts and media experts on the product developed, it was categorized as Very Good from both the material results and the valid results of the media. And based on the result of the questionnaire responses of the students given to 25 students, a total score of 229 was obtained from a maximum of 250. The average score per student was 9,16. If converted into a percentage, the result was 91,6%, which is included in the Very Practical category. Increase in the average value 80,60 points before treatment to 82,48 points after treatment still provides an indication that the method applied was able to provide a positive impact on students learning outcomes. Abstrak: Tujuan dari penelitian ini adalah untuk menghasilakan produk berupa buku mewarnai berbasis pembelajaran berdiferensiasi dan untuk melihat dampak buku tersebut terhadap kemamapuan peserta didik dalam pembelajaran calistung (membaca, menulis, berhitung) berdasarkan keanekaragaman gaya belajar peserta didik di kelas 2 Sekolah Dasar, dengan menggunakan materi pelajaran PKN sebagai materi yang digunakan dalam buku mewarnai tersebut. Metode penelitian yang digunakan dalam penelitian ini adalah Research and Development (R&D), dengan model ADDIE. Hasil akhir dari penelitian ini berupa buku mewarnai berbasis pembelajaran berdiferensiasi terhadap kemampuan calistung peserta didik di kelas 2 SDN 1 Kalijaga Selatan. Berdasarkan analisis hasil validasi tim ahli materi dan ahli media terhadap produk yang dikembangkan memperoleh kategori Sangat Baik. Dan berdasarkan hasil angket respon peserta didik yang diberikan kepada 25 peserta didik, diperoleh total skor keseluruhan sebesar 229 dari maksimal 250. Jika dikonversikan kedalam bentuk persentase, diperoleh hasil sebesar 91,6%, yang termasuk dalam kategori Sangat Praktis. Peningkatan nilai rata-rata dari 80,60 poin sebelum diberikan perlakuan menjadi 82,48 poin setelah diberikan perlakuan, hal ini tetap memberikan indikasi bahwa metode yang diterapkan mampu memberikan dampak positif terhadap hasil belajar peserta didik.